The year of sharing - Gilbert, Harry (Oxford Bookworms 2)
Richard is bored whith the quiet life of his village. He would like to have a motor - car and drive it... very fast. But Richard lives in a future world where there are no cars, only bicycles and small villages and green forests. And now he is twelve years old, and like the other children, he must do his Year of Sharing. He must live alone in the forest with the wild animals. He must learn no share his world; he must learn how animals live and eat fight... an die.